Sodium and Manganese Stoichiometry of P2‐Type Na2/3MnO2. Issue 41 (15th September 2016) - Kumakura, Shinichi; Tahara, Yoshiyuki; Kubota, Kei; Chihara, Kuniko; Komaba, Shinichi
Abstract: To realize a reversible solid‐state Mn III/IV redox couple in layered oxides, co‐operative Jahn–Teller distortion (CJTD) of six‐coordinate Mn III (t2g 3 –eg 1 ) is a key factor in terms of structural and physical properties. We develop a single‐phase synthesis route for two polymorphs, namely distorted and undistorted P2‐type Na2/3 MnO2 having different Mn stoichiometry, and investigate how the structural and stoichiometric difference influences electrochemical reaction. The distorted Na2/3 MnO2 delivers 216 mAh g −1 as a 3 V class positive electrode, reaching 590 Wh (kg oxide) −1 with excellent cycle stability in a non‐aqueous Na cell and demonstrates better electrochemical behavior compared to undistorted Na2/3 MnO2 . Furthermore, reversible phase transitions correlated with CJTD are found upon (de)sodiation for distorted Na2/3 MnO2, providing a new insight into utilization of the Mn III/IV redox couple for positive electrodes of Na‐ion batteries. Abstract : Highly reversible Na intercalation based on the Mn III/IV redox couple is demonstrated for Jahn–Teller‐distorted P2‐Na2/3 MnO2 and a non‐distorted form having Mn off‐stoichiometry. The distorted Na2/3 MnO2 delivers a higher energy of 590 Wh kg −1, accompanied by reversible phase transitions during Na extraction correlated with Na/vacancy ordering, charge order on Mn, and cooperative distortion.